Desenvolvimento e animação de atores sintético e articulados: uma simulação futebolística - QUINTO, Wanderson Alexandre da Silva (Universidade Federal do Pará, 2016)
This master’s dissertation aims to construct one 3D virtual environment in the form of a soccer stadium where simulations of a soccer game will be carried through, with the use of independent avatars. The construction of avatar use the H - Anim 1.1 modeling technique that it brings the concept of hierarchies and articulated body. The implementation of the application was developed with Java and API Java 3D. The autonomy is obtained by aid of Artificial Intelligence (AI) that it will act in the solution of the problems together with the use of rules previously known and tested. Intelligence, in this in case that, it can be observed by the use of three main components of the architecture of avatar: physical characteristics, behaviors and knowledge. For a better efficiency in the choice of which action avatar must make, was developed a strategy with assists of genetic algorithms that provides a better exactness.